FOUCAULTIAN PROVOCATIONS TO POLITICAL ECONOMY: AN INTRODUCTION TO THE HISTORY OF IDEAS - Santana, Marcelino de Carvalho (Passagens: Revista do Programa de Pós-Graduação em Comunicação da Universidade Federal do Ceará, 2024)
The objective of this article is to present part of Michel Foucault's (1926-1984) notes in relation to the history of ideas, with an emphasis on his circumspections regarding Political Economy. Taking his method, called “archaeology”, as a “starting point”, Foucault shows that during the period between the 17th and 18th centuries (classical age) it is possible to observe the presence of an “order of things”. This order concerns the interaction between the different primary notions of knowledge, from which the development of modern sciences, with emphasis on Political Economy, became possible. This observation made it possible to understand the movement between these primary forms, as well as their maintenance on the horizon, which produced a material extract of knowledge identified as episteme. Finally, we also sought to present the basic differences between the archaeological method and the conventional historical method, in addition to the objectives surrounding its formulation and its reception in the scientific world. KEYWORDS: Political Economy. Foucault. Wealth. Theory.